One-year predictors of PTSD symptoms, anxiety, and depression in SARS-CoV-2 survivors: psychological flexibility and major life events as main predictive factors - Carvalho, Sérgio A.; Pinto, Helena; Carreiras, Diogo; Palmeira, Lara; Pereira, Marco; Trindade, Inês A. (Frontiers in Psychology, 2024)
This project has been funded by the Social Observatory of the "la Caixa" Foundation as part of the "Call to support research projects on the social impact of covid-19" (2020).Outside of the current work, IAT has received consultancy fees from Pfizer Inc and speaking engagement fees from the Portuguese Inflammatory Bowel Disease Study Group (GEDII).The study was approved by the Ethics Committee of the Faculty of Psychology and Education Sciences of the University of Coimbra (15/09/2020), and was performed in accordance with the ethical standards as laid down in the 1964 Declaration of Helsinki and its later amendments.Informed consent was obtained from all participants, prior to participation in the study.